Ecosystem functions and management : theory and practice - Sandhu, Harpinder (Springer, 2017)
This is the first book to provide vital information on key local ecosystems, their functions, state of health, and their role in development in an Asian context, particularly on the Indian subcontinent. It addresses six major ecosystems on the Indian subcontinent - mountain, rural, desert, forest, urban, and freshwater - and discusses their functions, how they support livelihoods and the economy, the impacts on ecosystem services, and management issues. Asia is home to nearly one third of the global population. With massive industrialization occurring at an increasing pace to support the lifestyles of a growing population, impacts on natural ecosystems are inevitable in this region. The book also explores the concepts, theory and practice regarding these key ecosystems by linking them with the livelihoods of a large population base and subsequently illustrating their importance for sustainable development in the region. Further, by suggesting policies and ways in which these systems can be maintained and enhanced, it facilitates better management of natural resources within the ecological constraints to achieve socio-economic objectives and move towards a green economy for sustainable and equitable development in the region.